Building Bridges at the Science-Stakeholder Interface Towards Knowledge Exchange in Earth System Science (SpringerBriefs in Earth System Sciences,, 2018)
This book covers the approaches, applied methods and central participatory processes at the science-stakeholder interfaces embedded in the development of the "Earth System Knowledge Platform (ESKP)". The latter is an initiative of the German Helmholtz Association, synthesizing the expertise of the eight Helmholtz research institutions focusing on Earth System Sciences. The contributions showcase the approach of the Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research (AWI) within the ESKP initiative. Central focus is placed on the question as to which knowledge transfer processes can be employed to foster meaningful approaches based on science-stakeholder dialogues, data products, and/or modelling. The authors suggest that the tools and approaches for enhancing the vital contributions of science to addressing societal challenges warrant further investigation and development. .